Comparative Effects of Parent Management Training Combined With ACT and Mindful Parenting on Parent-child Relationship - Farzaneh Kosari; Parviz Sabahi; Shahrokh Makvand Hosseini (Gonabad University of Medical Sciences, 2024)
Background: Considering the profound influence of parent-child relationships on child vulnerability and mental health, prioritizing the improvement of this bond becomes crucial. While combined programs have garnered substantial recognition for their heightened effectiveness, regrettably, no research has yet explored a comparative analysis of their efficacy. This study aims to assess and compare the effectiveness of combining parent management training (PMT) with both acceptance commitment therapy (ACT) and mindful parenting in improving the parent-child relationship. Methods: The study employed a quasi-experimental design, specifically a pre-test and post-test method, with a three-month follow-up period. A control group was included to enhance the validity of the results. The statistical population comprised all mothers of preschool children in Semnan City, Iran in 2022. Using convenience sampling, 36 mothers were selected and randomly assigned to three groups, two experimental groups and one control group. Random assignment was achieved using a lottery-based method without replacement. The sample in experimental groups participated in an integrated training program, which consisted of two-hour sessions conducted eight times per week. Conversely, the control group was placed on a waiting list. The data analysis phase involved utilizing SPSS software, version 23 and applying multivariate covariance analysis.  Results: The results of the study indicated that both combined programs exhibited a significant impact on reducing conflicts within the parent-child relationship and fostering closeness (P<0.001). However, no significant effect was observed on parent-child dependency (P>0.05). Additionally, no significant difference was observed between the two combined programs regarding their effectiveness in enhancing the parent-child relationship. These results remained consistent during the follow-up stage.  Conclusion: This study highlighted that these programs have exhibited a significant capacity to enhance the parent-child relationship by fostering a sense of closeness and effectively mitigating conflicts. These results indicated that the integration of ACT or mindful parenting principles with PMT can provide valuable interventions for enhancing parent-child.